2009
DOI: 10.1038/nature07975
|View full text |Cite|
|
Sign up to set email alerts
|

Structural basis for leucine-rich nuclear export signal recognition by CRM1

Abstract: CRM1 (also known as XPO1 and exportin 1) mediates nuclear export of hundreds of proteins through the recognition of the leucine-rich nuclear export signal (LR-NES). Here we present the 2.9Å structure of CRM1 bound to snurportin 1 (SNUPN). Snurportin 1 binds CRM1 in a bipartite manner by means of an amino-terminal LR-NES and its nucleotide-binding domain. The LR-NES is a combined α-helical-extended structure that occupies a hydrophobic groove between two CRM1 outer helices. The LR-NES interface explains the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
391
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 294 publications
(410 citation statements)
references
References 50 publications
7
391
0
Order By: Relevance
“…Such an export mechanism has been identified, for example, in Snurportin-1. Snurportin-1 binds CRM1 in a bipartite manner, with a leucine-rich NES located in the N terminus and a second signal in a basic surface on the nucleotide binding domain (12). The second possibility is that CANCp2 and/or the full-length Gag protein forms or exposes one or more noncanonical determinants that are not formed by individually expressed MA, CA, or NCp2.…”
Section: Discussionmentioning
confidence: 99%
“…Such an export mechanism has been identified, for example, in Snurportin-1. Snurportin-1 binds CRM1 in a bipartite manner, with a leucine-rich NES located in the N terminus and a second signal in a basic surface on the nucleotide binding domain (12). The second possibility is that CANCp2 and/or the full-length Gag protein forms or exposes one or more noncanonical determinants that are not formed by individually expressed MA, CA, or NCp2.…”
Section: Discussionmentioning
confidence: 99%
“…by guest www.bloodjournal.org From RAN or cargo protein alone is weak, simultaneous binding of RAN and cargo to XPO1 increases its affinity to both by 1000-fold. 24,34 XPO1/RAN-mediated export is increased in a variety of cancers. Mechanistically, overexpression of XPO1 enhances export of nuclear tumor suppressor proteins such as p53, BRCA1, allophycocyanin, and NMP1, resulting in drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…This consensus sequence is found in PP32 LRRs 1-4, at least one of which is likely to interact with Crm1. Structures of Crm1 complexes have shown that the conserved Φ's of the consensus sequence dock into the pockets of the hydrophobic cleft of Crm1 (58,59). Because the conserved Φ's of PP32 make up its core and are not solvent-exposed, binding to Crm1 is likely to require partial unfolding of PP32.…”
Section: Possible Determinants For Folding Pathway Selections In Othementioning
confidence: 99%